Impact of Architectural Design Concept Source on Application Level of Interior Design - Issa, Naram Marquis; Khalil, Kadhim Fathel (Sulaimani Journal for Engineering Sciences, 2020)
Architectural education nowadays is considered one of the most important fields in architecture. The origin of learning in architecture is about the objective perception of the architectural concept in terms of its sources and levels of application. This research is generating from the question of the existence possibility effects of the architectural concept source in its application level to get to the essence that is forming from the architectural concept. The theories that dealt with this idea clarified a fragmented description which produces a knowledge gap. The problem statement of the research represented by the lack of knowledge that concerned with the effect of the architectural concept source on the application levels. The results of the case study were supporting the research hypothesis in the field of interior design. Cases were selected based on the clarity of their elements and levels of design. The search concluded that the concept source that is representing by the analogy symbolic concept, the analogy between nature and the project- was the most affected in the floor plan level.
Keywords: Architectural Concept; Interior Elements; Source of Concept; Analogy